Incidence of “Premature Sign-off” on Audit Procedure: Preliminary Analysis - Halil Paino; Siti Aisyah Mohd Amran (Communications of International Proceedings, 2020)
Audit role is significant in determining the fraudulent that occurred in corporate sectors by providing a quality audit report to assist the management in making effective and efficient decision to strengthen the business operation. Throughout the audit career path, completion of audit assignment within the time set by the audit manager is difficult to attain and gives greater pressure to audit staff. Hence, this problem may lead to Premature Sign-Off (PMSO) practices among the audit staff. PMSO occurs when an auditor signs off the required audit procedures without being covered by another procedure. This may lead to mitigating the effectiveness of audit process and compromising the audit quality. This paper examined the current level of incidence of PMSO among Malaysian external auditors, as well as to analyze the audit steps which appearing unnecessary, time budget constraint, inadequate supervision and readily accept the client explanation that affect the PMSO. Questionnaires were distributed to 125 audit firms in the Peninsular Malaysia and 99 responses were received. The result showed that, issues of PMSO definitely exist in Malaysia, and all the variables were significantly influenced the PMSO. Therefore, we should aware that the problem of PMSO exists in the audit environment, and preventive steps are needed to overcome this problem.
Keywords: Premature Sign-Off; Audit Steps Unnecessary; Time Budget Constraint; Inadequate Supervision; Readily Accept Client Explanation.